Study of Marriage Processions with Unequal Beliefs in The Perspective of Marriage Law in Indonesia - Nasution Dwi Shafira Chairunnisa; Fransiscus Xaverius Arsin (LEGAL BRIEF, 2022)
This study aims to further examine the rules governing interfaith marriages in Indonesia in terms of legal studies. The research method used is a normative approach using analysis of the study of legal material sources. The results of the study indicate that the rules contained in Law Number 16 of 2019 contain three binding articles, namely in article 1 which states that marriage must be based on the first principle of Pancasila, the second principle regulates the validity of marriage based on religious rules that and the third precept contains orders to carry out monogamous marriages. The existing rules are not prohibitive but are commanding and those who can determine whether a marriage is legal or not are from the respective religions. The background that underlies this research is the number of cases of interfaith marriages that occur in Indonesia so that it becomes a controversy in Indonesia.